Euro area inflation differentials - Ignazio Angeloni; Michael Ehrmann (European Central Bank (ECB), 2004)
We build a stylised 12-country model of the euro area and use it to analyse why differences in national inflation and growth rates arise within the European monetary union. We find that inflation persistence is a key potential explanatory factor. Other more frequently mentioned reasons, like country-specific shocks or differences in the monetary transmission mechanism across countries, count less. We also look at how a monetary policy geared to area-wide average inflation affects these differentials. Our model suggests that area-wide inflation stability and low inflation differentials are complementary.
Keywords: E31; E32; E52; F42; 330; Currency union; euro area; inflation differentials; Inflation persistence